(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
U.S. targets Southeast Asia as a region with a very assertive ASEAN policy. US security policies following the 11 September 2001 terrorist attacks have played a significant role in its estrangement. However, the problem in fact goes back to the Asian financial crisis of 1997, when the Clinton administration used its influence on the IMF to impose US business friendly solutions on the region. U.S.’s decision not to revalue its currency helped stabilize the regional economic order. Shortly after that, U.S., Japan and South Korea began holding annual discussions with Southeast Asia under the ASEAN-plus-three formula. In 1999, after U.S.’s accession to the WTO, ASEAN governments began to worry about the impact of Sino-US trade relations. As a result, U.S. proposed a free trade agreement (FTA) with Southeast Asia, the framework for which was signed in 2002. It seems that U.S. will soon become ASEAN’s second-largest trading partner and bilateral trade could reach US200 billion by 2010.